An Early Test-and-Treat Strategy for Severe Acute Respiratory Syndrome Coronavirus 2. (12th June 2020) - Schiffer, Joshua T; Johnston, Christine; Wald, Anna; Corey, Lawrence
Abstract: As coronavirus disease 2019 cases and deaths continue to expand globally, there is an urgent need to develop, test, and approve effective antiviral therapies. Currently, a majority of clinical trials are evaluating therapies in patients who are already hospitalized with severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) infection. Given that the median time between development of symptoms and need for hospitalization is 1 week, a golden opportunity to intervene early is being missed. Indeed, for many other viral infections, early treatment soon after development of symptoms is associated with decreased mortality, lower hospitalization rates, and lower likelihood of transmission to others. In this study, we advocate for randomized, double-blind, placebo controlled, clinical trials to evaluate promising agents early during SARS CoV-2 infection. Abstract : In this paper, we make the scientific argument for an increase in clinical trials treating SARS Co-V-2 early during infection. Early treatment of SARS-CoV-2 could disproportionately lower the mortality rate, but also lower hospitalization and decrease ongoing transmission of virus.